Pengaruh Pelatihan Kerja dan Pengembangan Karyawan Terhadap Kinerja Karyawan Melalui Kemampuan Kerja sebagai Variabel Mediasi - Jansen, Godelfridus Feneral; Endayani, Fatmasari; Setyawati, Dyah; Kustiani, Lilik; Lestari, Resanti (University of Merdeka Malang, 2023)
This study aims to explain the significant impact of job training and employee development on employee performance through work ability. The population in this study amounted to 60 employees who worked at PT Honda Dealer Sumber Purnama Sakti Batu. Data analysis was carried out using descriptive analysis and path analysis. The sampling technique used is saturated sampling technique. The results showed that there was a direct and indirect effect of job training and employee development variables on employee performance through job satisfaction. Of the two independent variables, employee development has the most dominant effect on employee performance through work ability.